Conformal Cu2S-coated Cu2O nanostructures grown by ion exchange reaction and their photoelectrochemical properties - Minguez-Bacho, Ignacio; Courte, Marc; Fan, Hong Jin; Fichou, Denis (Nanotechnology, 2015)
Cuprous oxide Cu2O is a promising p-type semiconductor for photoelectrochemical (PEC) solar hydrogen generation because it has a suitable bandgap (E-g = 2.0-2.2 eV) and a band alignment adapted to water reduction. In addition, metallic Cu is earth-abundant thus making Cu2O a low-cost material. However, the reduction potential of Cu2O into metallic Cu (0.47 V versus RHE) is lower than that of water which induces a severe instability under irradiation in a PEC cell. Therefore, our recent efforts focused on the growth of a protective overlayer on top of Cu2O in order to stabilize Cu2O when used as a photocathode in an aqueous electrolyte. Among potential protective materials cuprous sulphide Cu2S is another p-type semiconductor with a 1.2 eV bandgap and an appropriate energy level alignment with Cu2O that would allow electrons flowing to the interface. We present here an original and simple method aimed at protecting a compact layer (CL) or nanowires (NWs) of Cu2O with a Cu2S coating. Our method is based on the ions exchange reaction (IER) of O2- into S2- at the surface of Cu2O itself in a solution-containing Na2S as the sulphur source. The local surface IER implies the formation of a conformal and uniform coating independently on the starting Cu2O morphology, CLs or NWs. As expected, coating Cu2O photocathodes by a conformal Cu2S layer improves their stability and PEC performances.
Keywords: ion exchange reaction; photoelectrochemistry; nanomorphology; cuprous sulphide; cuprous oxide